Condutas conectada e separada dos tutores da UAB/UFSM nas atividades de estudo fórum no moodle - Teixeira, Tatiana Gloor (2013)
The aim is to comprehend how the tutors separate and connected conducts on the forum study activities at the Moodle enhance problem-posing dialogue and collaborative production regarding the curricular contents. The strategies implemented by the tutors on the forum study activities of the Distance Undergraduate Course in Letters Portuguese and Literatures of UAB/UFSM are problematized. The analysis of the tutors conducts on the forum study activities at the Moodle was conducted based on data obtained from survey type questionnaires, participant observation and course documents, according to the action research theoretical-methodological presuppositions. The research results indicate that the tutors separate and connected conducts, on the forum study activities at the Moodle, promote problem-posing dialogue and collaborative production as long as they develop fluency in the contents and in the technologies. In conclusion, it s pointed out that tutors separate and connected conducts, on the forum study activities at the Moodle, are elementary to enhance the problematization and the collaborative production of the UAB/UFSM courses curricular contents.